Economic feasibility of a sustainable production forest management system in Xaibouathong forest management area, Khammouan province, Lao PDR - Phayvanh Alounsavath Master; Se Bin Kim (Forest Science and Technology, 2021)
Sustainable Production Forest Management is a priority forest policy in Laos in which forest management plans need to be produced for each Production Forest Area (PFA). The forest management plan is very important for the sustainable use of forest resources in a PFA. It determines harvesting rotation cycles, annually allowed sustainable cuts of timber for each compartment, and identifies areas for conservation, restoration and rehabilitation in each PFA. This study examines the economic feasibility of the implementation of forest management operations in Xaibouathong Forest Management Area (FMA) in Khammouan Province with a 15-year cutting cycle. Data and information on Government cost norms, fees, and timber prices associated with the development and implementation of forest management plans, volumes and timber species harvested from three sub-forest management areas (Sivilai, Kengchone, and Phakong) of Xaibouathong FMA were collected and analyzed by using benefit-cost analysis. The results of this study showed that the current production forest management operation in Xaibouathong FMA is not economically feasible. Most of the sub-forest management areas costs outweigh its benefits because most of commercial tree species harvested in the three Sub-FMAs are lesser use species with low market price. Further study is needed to identify the real costs associated with the development and implementation of forest management plans when the Government permits logging operations in other production forest areas.